The Role of Caspase-3, Apoptosis-Inducing Factor, and B-cell Lymphoma-2 Expressions in Term Premature Rupture of Membrane - Ketut Surya Negara; Ketut Suwiyoga; Tjokorda Gede Astawa Pemayun; Anak Agung Raka Sudewi; Nyoman Mantik Astawa; I Gusti Nyoman Kamasan Arijana; Ketut Tunas (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To determine the role of caspase-3, apoptosis-inducing factor (AIF), and Bcell lymphoma-2 (Bcl-2) expressions in term premature rupture of membrane (PROM). Methods An analytic observational study with case-control design was conducted, involving 52 subjects (37-42 weeks of gestation) who were divided into 2 groups: 26 cases of term delivery with PROM, and 26 controls of term delivery without PROM. The expressions of caspase-3, AIF, and Bcl-2 in the amniotic membrane were determined by immunohistochemistry. Data were analyzed using the chi-squared test. The risk of PROM was expressed by odds ratio (OR). Results There were no significant differences in age, parity and body mass index between the two groups (p > 0.05). High caspase-3 and AIF expressions increased the risk of PROM 17.64 times (OR = 17.64; 95% CI = 4.44-70.07; p = 0.001) and 9.45 times (OR = 9.45; 95% CI= 2.62-34.07; p = 0.001), respectively, while low Bcl-2 expression increased 10.39 times (OR = 10.39; 95% CI = 2.73-39.56; p = 0.001)the risk of PROM . Conclusion High caspase-3 and AIF expressions and low Bcl-2 expression were risk factors for term PROM. Caspase-dependent and independent pathways of apoptosis were involved in the mechanism of PROM in term pregnancy.